EDUCATION DURING NATIONAL MOVEMENT IN JAVA 1908-1928 - Rofiatul Nur Jannah; Sumardi Sumardi; Nurul Umamah (History Education, University of Jember, 2018)
provided a variety of school education for indigneous people to obtain education. The error in this research is how is the education politics background education in Java the national movement of 1908-1928 ?, how is the system of education in Java the national movement of 1908-1928 ?. This research aimed to decrypt education in Java the national movement of 1908-1928. This research method is using historical research method by using approach of sociology of education. The benefits of this research, is expected to increase knowledge and can be used as a source of learning and can be used as a reference for further research. The conclusion that can be drawn from this research is first, Political education of Dutch colonial government in Java year 1908-1928 and education system in Java during national movement year 1908-1928.